The Next Wave of Deaths from Ebola? The Impact of Health Care Worker Mortality - Evans, David K. (World Bank E-Library Archive, 2015)
The ongoing Ebola outbreak in West Africa has put a huge strain on already weak health systems. Ebola deaths have been disproportionately concentrated among health care workers, exacerbating existing skill shortages in Guinea, Liberia, and Sierra Leone in a way that will negatively affect the health of the populations even after Ebola has been eliminated. This paper combines data on cumulative health care worker deaths from Ebola, the stock of health care workers and mortality rates pre-Ebola, and coefficients that summarize the relationship between health care workers in a given country and rates of maternal, infant, and under-five mortality. The paper estimates how the loss of health care workers to Ebola will likely affect non-Ebola mortality even after the disease is eliminated. It then estimates the size of the resource gap that needs to be filled to avoid these deaths, and to reach the minimum thresholds of health coverage described in the Millennium Development Goals. Maternal mortality could increase by 38 percent in Guinea, 74 percent in Sierra Leone, and 111 percent in Liberia due to the reduction in health personnel caused by the epidemic. This translates to an additional 4,022 women dying per year across the three most affected countries. To avoid these deaths, 240 doctors, nurses, and midwives would need to be immediately hired across the three countries. This is a small fraction of the 43,565 doctors, nurses, and midwives that would need to be hired to achieve the adequate health coverage implied by the Millennium Development Goals. Substantial investment in health systems is urgently required not only to improve future epidemic preparedness, but also to limit the secondary health effects of the current epidemic owing to the depletion of the health workforce